Women Mentorship Application using PHP/MySQL - Prof. Anand Ingle; Tejal Phadke; Ruchi Pakhale; Ainiya Shaikh; Anuja Sonawane (International Journal of Advanced Research in Science, Communication and Technology, 2023)
Almost 1 million engineers graduate each year in India, out of which only 15-20% are women which clearly depicts that women are highly underrepresented in STEM. It's 2022 and who says women can't do the same thing men can. Women can also pursue their passions, society is so close-minded that we don't see the potential that they have in their fields. I am a woman and I know what I am capable of and so should you! Gender inequality is everyone’s issue and not just a women's issue. India is a tough place for women even before they are born. Women are not even accepted as human beings, they are treated with injustice and inequality, and they are denied and neglected even in developed countries. Right from childhood women face lots of struggles right from the time they are born, in rural areas people do not even consider educating or sending their daughters to higher studies, WHYYYYY??? Keeping this problem in mind, we have developed an application called Potenshe which is a web application designed to help women unleash their inner power to advance their skillset, rights, and opportunities for women around the globe. Our aim is to bridge the gender inequality gap and intersecting issues, connect with leaders around the world, and access opportunities in the area nearest to their location!